Prevalence of obesity and cardiovascular risk among children and adolescents in the municipality of Santa Cruz do Sul, Rio Grande do Sul - Reuter, Cézane Priscila; Burgos, Leandro Tibiriçá; Camargo, Marcelo Dias; Possuelo, Lia Gonçalves; Reckziegel, Miriam Beatris; Reuter, Éboni Marília; Meinhardt, Francielle Pasqualotti; Burgos, Miria Suzana (São Paulo Medical Journal, 2013)
CONTEXT AND OBJECTIVE: Studies have demonstrated that metabolic complications from child obesity, although silent, increase the risk of development of cardiovascular diseases in adulthood. The present paper sought to describe the prevalence of overweight/obesity and analyze the possible relationship between obesity and other cardiovascular risk factors among children and adolescents. DESIGN AND SETTING: Cross-sectional study, conducted in a university. METHODS: The study included 564 children and adolescents, aged 8 to 17 years. Body mass index and waist circumference were used to evaluate obesity. Other cardiovascular risk factors were evaluated, like systolic and diastolic blood pressure, glycemia, triglycerides and total cholesterol. Descriptive analysis was used for sample characterization, the chi-square test for categorical variables and Pearson’s linear correlation for evaluating the relationship between obesity indicators and other cardiovascular risk factors. RESULTS: High prevalence of overweight/obesity was found among the schoolchildren (25.3% among the boys and 25.6% among the girls), along with abdominal obesity (19.0%). The overweight/obese schoolchildren presented higher percentages for the pressure and biochemical indicators, compared with underweight and normal-weight schoolchildren. Body mass index and waist circumference showed a weak correlation with the variables of age and systolic and diastolic blood pressure (P < 0.001), but there was no correlation between these obesity indices and biochemical variables. CONCLUSION: The high prevalence of overweight/obesity and its relationship with other cardiovascular risk factors demonstrate that it is necessary to develop intervention and prevention strategies from childhood onwards, in order to avoid development of chronic-degenerative diseases in adulthood.